Prenatal diagnosis and management of congenital diaphragmatic hernia. (July 2019) - Basurto, David; Russo, Francesca Maria; Van der Veeken, Lennart; Van der Merwe, Johannes; Hooper, Stuart; Benachi, Alexandra; De Bie, Felix; Gomez, Olga; Deprest, Jan
Abstract: Congenital diaphragmatic hernia is characterized by failed closure of the diaphragm, thereby allowing abdominal viscera to herniate into the thoracic cavity and subsequently interfering with normal lung development. At birth, pulmonary hypoplasia leads to respiratory insufficiency and persistent pulmonary hypertension (PHT), that is lethal in up to 32% of patients. In isolated cases, the outcome may be predicted prenatally by medical imaging and advanced genetic testing. In those fetuses with a predicted poor outcome, fetoscopic endoluminal tracheal occlusion may be offered. This procedure is currently being evaluated in a global randomized clinical trial (www.TOTALtrial.eu ). We are currently investigating alternative strategies including transplacental sildenafil administration to reduce the occurrence of persistent PHT. Highlights: Prenatal imaging and genetic testing are essential when CDH is suspected. Micro arrays detect 9% of disorders missed by karyotype. Targeted resequencing identified an extra 10% in archived samples. Lung size, liver herniation and stomach position are good predictors of survival. A prenatal predictor of persistent pulmonary hypertension is still lacking. FETO remains experimental and should be offered in the frame of the TOTAL trial.